Comparing Spatial Welfare Among Major Cities in Java - Firdha Kusuma Wardani; Evi Gravitiani; Tetuko Rawidyo Putro (EKO-REGIONAL, 2023)
Education, economy, health, tourism, industry, transportation, and social welfare were greatly affected by the 2021 Covid-19 Pandemic. The benchmark for welfare is properly fulfilling the basic needs of society. This study aims to model the level of social welfare in big cities on the island of Java in 2021 by including spatial effects. The method used is Ordinary Least Square (OLS) and Geographically Weighted Regression (GWR). GWR model, the weighting used is the Gaussian kernel function. The OLS model produces an R2 of 83.96%, while the GWR model produces an R2 of 84.03%. This shows that the GWR model is better at explaining the level of diversity in the welfare of cities on the island of Java, which is 84.03% and the rest is influenced by geographical factors because there is no significant difference between the linear regression model and GWR.